The demand for data skills in German companies: Evidence from online job advertisements - Jan Büchel; Jan Engler; Armin Mertens (EconPol Forum, 2023)
Data skills are required in every fifth online job advertisement in Germany. Demand for data skills is increasing over time and heterogenous between sectors. Companies from the ICT sector demand more advanced data skills in every second job advertisement. Sectors that are advanced in digitalization have a higher demand for jobs with data skills. Policymakers should intensify the recruitment of foreign professionals and align curricula with growing business demand for data skills.
Keywords: 330